FHG-PR: a hybridized fuzzy-AHP and game theory model for assessing privacy risk on social media platforms - Falana, Olorunjube James; Ojeaga, Trust; Naeem, Hamad; Aborisade, Dada Olaniyi; Alsirhani, Amjad; Alserhani, Faeiz (Frontiers in Computer Science, 2024)
Social media platforms have become integral to our daily lives, enabling global connectivity and interaction. However, the voluntary sharing of personal information on these platforms introduces significant privacy risks, highlighting the need for effective risk assessment mechanisms. Existing research often addresses broad risk mitigation strategies but lacks a focused assessment of specific platforms like Meta and X. This paper introduces a hybrid privacy risk assessment model combining fuzzy Analytical Hierarchy Process (AHP) and game theory to evaluate and mitigate privacy invasion risks on these platforms. By surveying social media users and professionals to prioritize determinant criteria, the study applies fuzzy AHP to weigh these criteria and utilizes a multi-criteria decision-making (MCDM) framework based on cooperative game theory to propose alternative strategies for risk reduction. The findings demonstrate that the proposed model offers practical strategic options to reduce privacy breaches of sensitive data on social media.